Pengaruh Ice breaking terhadap Konsentrasi Belajar Anak pada Mata Pelajaran Pendidikan Agama Islam - Lubis, Ayang Ratu Nita; Zuhri, Zuhri; Afriani, Gusma (Absorbent Mind, 2025)
Good concentration is essential in the learning process, as it enables children to absorb information more effectively and retain it for longer periods. This study investigates the impact of ice-breaking activities on students' learning concentration in Islamic Religious Education at State Senior High School 10 Pekanbaru. The research employs a quantitative approach with a Quasi-Experimental method, utilizing a Non-Equivalent Control Group Design. The study sample consisted of 35 students from class X.1 as the experimental group and 35 students from class X.3 as the control group, selected through a purposive sampling technique. Data collection methods included observation, questionnaires, and documentation. Data analysis was conducted using parametric statistics with the T-test. The findings reveal a significant difference in learning concentration between the control and experimental groups in Islamic Religious Education. The t-value (t_count) was 3.987, exceeding the critical t-value (t_table) of 1.667, with a significance value of 0.000 < 0.05, leading to the rejection of H_0 and acceptance of H_a.